1983
DOI: 10.1002/aja.1001680204
|View full text |Cite
|
Sign up to set email alerts
|

Development and melatonin content of the deep pineal gland in the syrian hamster

Abstract: The morphological relationships between the superficial and deep pineal glands of neonatal Syrian hamsters are described at both light and electron microscopic levels. In addition, melatonin contents in the two glandular masses are compared throughout a 14 hr light:10 hr dark photoperiod in 20-day-old hamsters. It has been found that the pineal anlage begins to separate into deep and superficial components between the first and third postnatal days of life. Separation is usually complete by day 12. The fine st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

1984
1984
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
1
9
0
1
Order By: Relevance
“…In the preliminary study we found that the nocturnal elevation of pineal and circulating melatonin in the strain of hamsters used by us occurred at about 0200 h. This agreed with a couple of published reports [Sheridan and Rollag, 1983; Rollag and Stetson, 19811. Tamarkin et al [ 19801 selected the nocturnal peak time point of 2200 h for pineal melatonin, basing their expectation on previous work with adult hamsters [Wilkinson et al, 1977;Tamarkin et al, 19791. However, in our species the 2300 h level was found to be lower than the 0200 h level.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the preliminary study we found that the nocturnal elevation of pineal and circulating melatonin in the strain of hamsters used by us occurred at about 0200 h. This agreed with a couple of published reports [Sheridan and Rollag, 1983; Rollag and Stetson, 19811. Tamarkin et al [ 19801 selected the nocturnal peak time point of 2200 h for pineal melatonin, basing their expectation on previous work with adult hamsters [Wilkinson et al, 1977;Tamarkin et al, 19791. However, in our species the 2300 h level was found to be lower than the 0200 h level.…”
Section: Discussionsupporting
confidence: 89%
“…The current report on the ontogenesis of the synthesis of various pineal compounds in Syrian hamster and their release in the circulating system agrees as well as disagrees with the few reports so far published on this topic. In the preliminary study we found that the nocturnal elevation of pineal and circulating melatonin in the strain of hamsters used by us occurred at about 0200 h. This agreed with a couple of published reports [Sheridan and Rollag, 1983; Rollag and Stetson, 19811 Tamarkin et al, 19791. However, in our species the 2300 h level was found to be lower than the 0200 h level. Although pineal melatonin was detectable in the animals at 5 days of postnatal age, significant day-night differences occurred only at 25 days of age.…”
Section: Discussionmentioning
confidence: 99%
“…At P30, a significant day/night rhythm in AA‐NAT activity is observed, which is consistent with published values (18). The elaboration of the daily rhythm in pineal activity could depend on the sympathetic fibres invasion in the pineal, which starts at the end of the first week of life (31) and is complete at approximately P15 in Syrian hamsters (32). However, this correlation is questionable since Tamarkin et al .…”
Section: Discussionmentioning
confidence: 99%
“…The pineals were quickly dissected, frozen in liquid nitrogen and stored at --80 ~ until determination. Because in the deep pineal neither HIOMT activity nor aMT content could be detected (P6vet et al, 1980;Sheridan and Rollag, 1983), only the superficial pineal gland was dissected. After dissection of the pineal gland, both testes were removed and weighed immediately.…”
Section: Methodsmentioning
confidence: 99%